LEADING SECTORS AND REGIONAL SPECIALIZATION: LEARN FROM INDONESIAN ECONOMY - Abd. Rahman R, Sabir, Muhammad Arsyad (International Journal of Advanced Science and Technology, 2020)
Leading sectors and regional specialization become a central point in the economy. The study aimed to measure the ability to lead sectors in creating regional specialization in each province in Indonesia. The analysis employed Location Quotient (LQ), Growth Ratio Model (MRP), and Krugman Index for all of 34 provinces in Indonesia. The results show that all provinces in Indonesia have superior sectors vary in number and type, both in terms of their contribution to the GRDP as well as in growth aspects, so it is very likely to form regional specialization. This situation has been able to be exploited by the Riau Islands and East Kalimantan Provinces by forming a dominant regional specialization. They have a strong economic linkage with more other provinces. However, there are still more provinces that have not been able to utilize their leading sectors to form regional specializations in order to build broader economic linkages with other provinces. The provinces include Aceh, North Sumatra, West Sumatra, Southeast Sulawesi, South Kalimantan, and Central Kalimantan Provinces. DKI Jakarta Province, as the capital city of the country, is highly expected to have a dominant regional specialization, creating broader economic linkages with the other provinces. Therefore, it is necessary to change the direction of the regional leading sector development in the provinces concerned, to encourage regional specialization creation and their economic linkages among provinces in the future.